Controlled synthesis of two-dimensional (2-D) ultra-thin bismuth selenide (Bi2Se3) nanosheets by bottom-up solution-phase chemistry and its electrical transport properties for thermoelectric application - Bin Masood, Khalid; Kumar, Pushpendra; Giri, Rajiv; Singh, Jai (FlatChem, 2020)
Bismuth Selenide and associated compounds inheriting stacked layered structure represent a unique class of materials where bulks are insulating with conducting surfaces, best known as thermoelectric materials. The bottom-up solution-based approach is a convenient alternative producing ultrathin high quality two-dimensional Bi2Se3 nanosheets. The present investigation deals with glycol mediated synthesis of highly crystalline ultrathin Bi2Se3 nanosheets. The as-synthesized Bi2Se3 nanosheets exhibit a rhombohedral crystal structure with a substantial surface-to-volume ratio that can possess several potential applications. Besides, the ultrathin Bi2Se3 nanosheets produced herein, found to be n-type with robust spatial confinement of charge carriers advantageous for thermoelectric applications, delivering a high-power factor of 1.55 mu W/cmK(2) at 150 degrees C. The method demonstrates the generic feature of the solution phase technique for the synthesis of highly crystalline nanosheets allowing mass production of identical ultra-thin nanosheets that can be easily integrated into devices for several promising applications, including spintronics, energy storage, and topological quantum computation.
Keywords: Rhombohedral structure; Sheet-like structure; Thermoelectric nanomaterials; transmission electron microscopy; XPS Spectra

Electrochemical performance of pre-lithiated ZnMoO4 and r-GO@ZnMoO4 composite anode for lithium-ion battery application - Bin Masood, Khalid; Parte, Golu; Jain, Neha; Dwivedi, Pravin K.; Kumar, Pushpendra; Shelke, V, Manjusha; Patel, Rp; Singh, Jai (Journal of the Taiwan Institute of Chemical Engineers, 2020)
Exploring a safer replacement of Li metal anode is crucial for technological, and fundamental importance. Li-metal is a preferred choice as anode material for lithium-ion battery (LIB) applications. However, parasitic dendritic growth on the Li metal surface during cycling causes instability and safety dreads. In the present study, we have investigated that the pre-lithiated ZnMoO4 is superior to its carbon-based counterparts (r-GO@ZnMoO4), moreover safer and sustainable than Li metal anode. The pre-lithiated ZnMoO4 delivers a better reversible capacity (similar to 1000 mAhg(-1) at 0.1 Ag-1), superior rate capability (similar to 400 mAh g(-1) at 2 Ag-1), and excellent cycling stability over 300 cycles at 0.1 Ag-1, as compared to bare ZnMoO4 and r-GO@ZnMoO4 composite. The present investigation is an attempt to provide a substitute for commonly used Li-metal/carbon anodes with better performance. (C) 2020 Taiwan Institute of Chemical Engineers. Published by Elsevier B.V. All rights reserved.
Keywords: Cycling stability; Electrochemistry; Li-ion battery; Nyquist plot; Rate performance; ZnMoO4 nanocomposites